A short history of India's economy: A chapter in the Asian drama - Kaushik Basu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper is a short history of the Indian economy since 1968. India today is a changed country from what it was half a century ago, when Myrdal published his Asian Drama. The stranglehold of low growth has been broken, its population below the poverty line has fallen markedly, and India has joined the pantheon of major players globally. This paper analyses the economic policies and the politics behind this transformation; and uses that as a backdrop to take stock of the huge challenges that lie ahead.
Keywords: A12; B10; B31; N14; O10; 330; India; growth history; political economy; corruption; technological change